Report of the Working Group on Health Education & IEC for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
Healthcare delivery in India faces significant challenges, with nearly half the population lacking access to basic services and urban-centric infrastructure limiting local participation. The ICSSR/ICMR report of 1981 emphasizes health as a multi-dimensional concept encompassing socio-economic factors such as nutrition, education, sanitation, and employment. Strengthening community involvement through training local health functionaries, integrating indigenous practices, and leveraging Panchayati Raj governance is essential for effective health promotion and early intervention. The report recommends centrally sponsored programs, community-based health education, continuous training, and pilot projects to validate strategies, advocating a transformative approach to achieving “Health for All” through culturally sensitive, locally driven initiatives.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Healthcare Delivery; Community Involvement; India; Local Health Functionaries; Primary Health Care; Panchayati Raj; Health Education; Indigenous Practices; Public-Private Partnership; Socio-Economic Health; Health Promotion; Decentralized Governance